Public pensions and implicit debt: An investigation for EU member States using Ageing Working Group 2021 projections - Georgios Symedonidis; Platōn Tēnios; Michail Chouzouris (Risks, 2021)
Ιmplicit pension debt is attracting increasing attention worldwide as a driver of fiscal dynamics, operating in parallel to the (explicit) National Debt. A prudent examination of a state's fiscal prospects should ideally encompass both, with due attention paid to the special features of each kind of debt. The explosion of government deficits as a result of the COVID-19 pandemic only adds to the urgency of understanding the scale and nature of issues around accounting for contingent liabilities. The reports of the EU Ageing working group, produced and published every three years are used to derive estimates of the stock of outstanding implicit pension debt from flows of projected deficits. This can be performed for all European member states. This paper uses the last two rounds of the Ageing Report (2021, 2018) and derives conclusions on the evolution of pension debt and its correlation to the external debt. The paper concludes that producing comparable estimates of IPD should become an important input in EU policy discussion.
Keywords: 330